Performance objectives of public private partnership implementation in Malaysia: Perception of key players - Mohamad, Rosnani; Ismail, Suhaiza; Mohd Said, Julia (Emerald Publishing Limited, 2018)
Purpose – The objectives of this present study are twofold. First, it aims to investigate the performance objectives of PPP implementation in Malaysia. Second, it aims to examine the differences in the perceptions of two PPP key players – the public and private sectors – pertaining to the performance objectives. Design/methodology/approach – A questionnaire survey was used to elicit the perceptions of the public and private sectors concerning the performance objectives of PPP projects in Malaysia; 237 usable responses were obtained and analysed using SPSS to rank the importance of the performance objectives and to examine the differences in the perceptions between the government and private sectors. Findings – The results reveal that the five most important performance objectives for PPP implementation in Malaysia based on overall respondents’ perceptions are “High-quality public service”, “Provide convenient service for society”, “Within or under budget”, “On-time or earlier” and “Satisfy the need for more public facilities”. As for differences in the perceptions of the two key players, only one objective was perceived as statistically more important by the public sector respondents than by their private sector counterparts. Originality/value – The contribution of this paper is that it not only provides empirical evidence for the performance objectives for PPP implementation in Malaysia, but also offers evidence concerning the differences in the perceptions of the public and private sectors pertaining to the performance objectives